Application of genetic markers to forest tree species: Draft report to IPGRI of the project Developing Decision-making Strategies on priorities for conservation and use of forest genetic resources - Namkoong, G.; Koshy, M.P. (2001)
The application of genetic markers such as allozymes and DNA (Deoxyribose Nucleic Acid) markers has shown to be useful in studying genetic diversity in humans, animals and plants (Cruzan, 1998). This section of this manual attempts to give guidelines for choosing appropriate molecular tools for the study of genetic variation in species under different conservation status. In general, forest trees can be categorized as totally wild species , trees of economic importance (both un- or semi- domesticated species) and lastly, model forest trees, which are being intensively managed through tree breeding.